Pengaruh Inflasi, Suku Bunga dan Rasio Keuangan terhadap Harga Saham - Denia Maulani; Desmy Riani (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2021)
Purpose This study was conducted to see the extent of the influence of external factors on the rate of inflation, interest rates and internal factors by using the company's financial ratio indicators on the ratio of earnings per share (EPS), return on assets (ROA), price earning ratio (PER), debt to equity ratio (DER) and return on equity (ROE) for companies in the financial industry on the Indonesia Stock Exchange (IDX) in 2015-2019. Methodology Testing is done by using panel data regression. The sampling technique used is by using purposive sampling. The objects in this study are companies listed in the financial industry on the Indonesia Stock Exchange in 2015-2019 using panel data regression. Findings The research findings show that partially only EPS and PER variables have a positive and significant effect on stock prices. Simultaneously the inflation rate, interest rates, EPS, ROA, PER, DER and ROE have a significant effect on stock prices. Suggestion In further research, it can be tested using other variables that have a strong relationship with stock prices.